Cellulose, pectin and water in cell walls determine apple flesh viscoelastic mechanical properties. (15th March 2020) - Lahaye, Marc; Falourd, Xavier; Laillet, Brigitte; Le Gall, Sophie
Highlights: The viscoelastic mechanical properties of fresh and plasmolyzed apple are reported. Damping (tan∂) and storage modulus (E') are related. Plasmolyzed apples are better distinguished by the relation between tan∂ and E'. Cell wall galactose and arabinose relation with E' distinguish two groups of apples. Cellulose C4 NMR mobility is related with E': firm apples have disordered cellulose. Abstract: The viscoelastic mechanical properties are important quality traits for fleshy fruit uses. The contribution of cell wall polysaccharides chemistry and organization on their variability was studied in six varieties of apple. Correlation between damping and storage modulus of plasmolyzed tissue distinguished better apple varieties on their viscoelasticity than fresh samples. Galactose, arabinose and uronic acids correlated positively with the storage modulus of fresh apple samples (E'f ). These corresponded to 4-linked galactan but no specific arabinose linkage. Galacturonic acid branched on O-3 and terminal rhamnose correlated negatively with E'f . These correlations formed two groups of fruit except for branched methyl-esterified galacturonic. Solid-state 13 C NMR spectroscopy analyses showed that E'f correlated negatively with cellulose C4 T 1 ρ H relaxation and positively with pectin methyl esters T H H proton diffusion. The results point to the key roles of pectin structure and hydration and cellulose microfibrils distribution on apple mechanical properties.